Gender influence on the adoption of family - friendly policies by businesses in Kenya - Wahome, Rose W. (Strathmore University, 2009)
A woman’s career faces many challenges especially if she is married due to the numerous demands on her as a wife and mother. In traditional society, the man was the sole bread winner for the family. Women were socialized as home-makers whose chores revolved around the family and bringing up children. However, the 20th century, there was a dramatic shift in the workforce that saw many women take up employment to supplement their families’ income. Since then, there has been an upward trend in the number of women seeking college education and joining the workforce. There is evidence that women have talents and skills that contribute positively to business performance previous studies reveal that firms with a majority of women on board of directors, experience higher financial performance. Recently, women have been rising to the top echelons of business management without having to sacrifice their families’ well being due to the implementation of family-friendly policies (FFPs). These policies include parental leave, flexi time and working from home. More firms appreciate the need for diversity in the business arena and are advocating for family friendly policies that allow women to lead business as they raise their families. When women receive support from their families (spouses) and business firms, they are able to manage both responsibilities. However, the adoption of family friendly policies in firms remains a controversial issue as some schools of though argue that the implementation of such policies will harm the bottom line. The study presupposes that women Human Resource (HR) managers have a stronger positive influence on the adoption of family-friendly policies as they understand their fellow women’s challenges better. However, the results indicate that the gender of the Human Resource Manager does not play a significant role in the adoption of Family Friendly policies. Rather, it is the involvement of the women within the organization in coming up with ways to reduce the impact of family friendly policies on the bottom line.
Partial fulfillment for award of Master of Business Administration
Keywords: Women employment--Kenya